REMUNERASI, BUDAYA ORGANISASI DAN KINERJA PEGAWAI - Eddy Hazmi; Sujianto Sujianto; Zaili Rusli (Universitas Riau, 2018)
Remuneration, Organizational Culture and Employee Performance. This research uses quantitative descriptive method. The population is 481 people and the sample is 83 people. Data collection techniques are questionnaires, interviews and observations. Data analysis using multiple linear regression. The results showed that Remuneration and organizational culture simultaneously have a positive and significant effect on employee performance on University of Riau Campus. Partially, each variable of remuneration and organizational culture have a positive and significant effect on employee performance on University of Riau Campus, while organizational culture variable is the most dominant variable affecting employee performance on University of Riau Campus. Based on the results of Coefficient of determination test shows that variable remuneration and organizational culture able to influence employee performance variable at the University of Riau Campus of 88.0% and the rest of 12.0% explained by other independent variables not examined.